Cellular immune breadth of an Omicron-specific, self-amplifying monovalent mRNA vaccine booster for COVID-19 - Durgesh Kumar; Kishor Gaikwad; Rushank Gunnale; Sandeep Vishwakarma; Shalu Shukla; Shalini Srivastava; J. Gopal; Bijay Vaidya; Amit Saraf; Rohan Gurjar; Swarnendu Kaviraj; Ajay Singh; et al. (2025)
Selecting a booster vaccine strategy that generates cellular immune breadth is crucial for effectively recalling cellular reservoirs upon infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) variants. This post hoc analysis from a multicentre, randomized phase 3 study (CTRI/2022/10/046475) compared the cellular immune breadth induced by self-replicating mRNA (samRNA) vaccine GEMCOVAC-OM, encoding Omicron B.1.1.529 Spike protein, with the adenovector vaccine ChAdOx1 nCoV-19, encoding Wuhan variant Spike protein, when administered as a booster. GEMCOVAC-OM elicited significant expansion of memory B-cells (MBCs) specific to Omicron B.1.1.529, compared to ChAdOx1 nCoV-19. GEMCOVAC-OM also induced more B-cells reactive to Omicron XBB.1.5 and BA.2.86 Spike proteins. Additionally, GEMCOVAC-OM triggered higher frequencies of Omicron-Spike-specific T-cells, including stem cell, central, and effector memory subsets. In summary, while ChAdOx1 nCoV-19 showed some cross-reactivity, GEMCOVAC-OM induced a more targeted immune response. GEMCOVAC-OM offers a broader, longer-lasting immunity, making it a promising candidate for future vaccine development and global distribution.